Theorem.Suppose xn→x and yn→y. Then xn+yn→x+y.
Proof. Let ϵ>0.
1◯∃Nx:n>Na⟹∣xn−x∣2◯∃Ny:n>Ny⟹∣yn−y∣<2ϵ<2ϵxn→xyn→y
Thus, for all n>N=max(Nx,Ny), we have
∣xn+yn−(x+y)∣≤∣xn−x∣+∣yn−y∣<ϵTriangle inequality1◯,2◯
Theorem.Suppose xn→x and yn→y. Then xnyn→xy.
Proof. First, let’s establish an identity:
xnyn−xy=xnyn−xny+xny−xy=xn(yn−y)+y(xn−x)=(xn−x+x)(yn−y)+y(xn−x)=(xn−x)(yn−y)+x(yn−y)+y(xn−x)
Now, let ϵ>0.
1◯∃Nx:n>Nx⟹2◯∃Ny:n>Ny⟹∣xn−x∣<3ϵ+3∣y∣ϵ∣yn−y∣<3ϵ+3∣x∣ϵxn→xyn→y
Thus, for all n>N=max(Nx,Ny), we have
∣xnyn−xy∣=∣(xn−x)(yn−y)+x(yn−y)+y(xn−x)∣≤∣xn−x∣∣yn−y∣+∣x∣∣yn−y∣+∣y∣∣xn−x∣<3ϵ+3ϵ+3ϵ=ϵIdentity aboveTriangle inequality1◯,2◯
In the construction of N above, note that we are assuming x,y=0. If either is zero, the second term in the sum can simply be omitted, as the corresponding term below is zero.
Theorem.Suppose xn→x, with xn=0 for all n and x=0. Then 1/xn→1/x.
Proof.
First, let us note that ∣a−b∣<21∣b∣⟹∣a∣>21b. This is fairly obvious when you think about it; to prove it, we can break the claim up into cases:
The cases where b<0 follow the same reasoning. Now, let ϵ>0.
1◯2◯3◯∃N1:n>N1⟹∣xn−x∣∃N2:n>N2⟹∣xn−x∣so that ∣xn∣<21∣x∣2ϵ<21∣x∣>21∣x∣xn→xxn→x2◯,see above
Thus, for all n>N=max(N1,N2), we have
∣xn1−x1∣=∣xnxx−xn∣≤∣x∣22∣xn−x∣<ϵ3◯1◯
Note that in this third theorem, the requirement that xn=0 is unnecessary. As we see from 3◯, if xn→x and x=0, then there is an N such that xn=0 for all n>N.
Continuity
The first two theorems are essentially the same as their sequence counterparts, but the differences are worth paying attention to.
Theorem.Let the functions f and g be continuous at x0. Then h=f+g is continuous at x0.
Proof. Let ϵ>0.
1◯∃δf:∣x−x0∣<δf2◯∃δg:∣x−x0∣<δg⟹∣f(x)−f(x0)∣<2ϵ⟹∣g(x)−g(x0)∣<2ϵf continuous at x0g continuous at x0
Thus, for all x:∣x−x0∣<δ=min(δf,δg), we have
∣h(x)−h(x0)∣=∣f(x)+g(x)−f(x0)−g(x0)∣≤∣f(x)−f(x0)∣+∣g(x)−g(x0)∣≤ϵDef hTriangle inequality1◯,2◯
Theorem.Let the functions f and g be continuous at x0. Then h=f⋅g is continuous at x0.
Proof. Let ϵ>0.
1◯∃δf:∣x−x0∣<δf2◯∃δg:∣x−x0∣<δg⟹∣f(x)−f(x0)∣<3ϵ+3∣g(x0)∣ϵ⟹∣g(x)−g(x0)∣<3ϵ+3∣f(x0)∣ϵf continuous at x0g continuous at x0
Thus, for all x:∣x−x0∣<δ=min(δf,δg), we have
∣h(x)−h(x0)∣=∣f(x)g(x)−f(x0)g(x0)∣≤∣{f(x)−f(x0)}{g(x)−g(x0)}∣+∣f(x0){g(x)−g(x0)}∣+∣g(x0){f(x)−f(x0)}∣<3ϵ+3ϵ+3ϵ=ϵDef hSee earlier proof1◯,2◯
Theorem.Let the function f be continuous at x0 and the function g be continuous at f(x0). Then h(x)=g(f(x)) is continuous at x0.
Proof. Let ϵ>0.
1◯∃η:∣y−f(x0)∣<η2◯∃δ:∣x−x0∣<δ⟹∣g(y)−g(f(x0))∣<ϵ⟹∣f(x)−f(x0)∣<ηg continuous at f(x0)f continuous at x0
Thus, for all x:∣x−x0∣<δ, we have
∣h(x)−h(x0)∣=∣g(f(x))−g(f(x0))∣<ϵDef h2◯⟹1◯
Exercise: Write an R function n(eps) that returns the smallest N for which n>N⟹∣f(xn)−f(x0)∣<ϵ for xn=21/n and f(x)=ex.
Conceptually, this is a three-part process:
Determine what xn is converging to. Here, xn→1.
Determine the largest value of delta that satisfies e1+δ−e1<ϵ.
Determine the smallest value of N such that 21/n−1<δ.
n <-function(eps) { delta <-log(eps +exp(1)) -1ceiling(1/log2(1+delta))}
Let’s test this out and make sure it works:
n(0.01)## [1] 190exp(2^(1/189)) -exp(1) ## 189 not good enough## [1] 0.01000582exp(2^(1/190)) -exp(1) ## 190 within 0.01## [1] 0.009952969